COVID-19 vaccination coverage and its cognitive determinants among older adults in Shanghai, China, during the COVID-19 epidemic - Lu Wei; Wu Zeng; Yangyang Huang; Guoxin Ye; Ying Chen; Ling Yang; Ling Yang; Yuyang Cai (Frontiers Media S.A., 2023)
ObjectivesThis study aimed to examine the coverage of coronavirus disease 2019 (COVID-19) vaccination and its cognitive determinants among older adults.MethodsA cross-sectional study was conducted using a questionnaire to conduct a survey among 725 Chinese older adults aged 60 years and above in June 2022, 2 months after the mass COVID-19 outbreak in Shanghai, China. The questionnaire covered demographic characteristics, COVID-19 vaccination status, internal risk perception, knowledge, and attitude toward the efficacy and safety of COVID-19 vaccines.ResultsThe vaccination rate was 78.3% among the surveyed individuals. Self-reported reasons for unwillingness to get vaccinated (multiple selections) were "concerns about acute exacerbation of chronic diseases after vaccination (57.3%)" and "concerns regarding vaccine side effects (41.4%)." Compared to the unvaccinated group, the vaccinated group tended to have a higher score in internal risk perception (t = 2.64, P < 0.05), better knowledge of COVID-19 vaccines (t = 5.84, P < 0.05), and a more positive attitude toward the efficacy and safety of COVID-19 vaccines (t = 7.92, P < 0.05). The path analysis showed that the cognitive effect on vaccination behavior is relatively large, followed by the internal risk perception, and then the attitude toward COVID-19 vaccines. The more knowledgeable the participants were about COVID-19 vaccines, the more likely they were to receive the COVID-19 vaccines. In the multivariate logistic regression, the increased coverage of COVID-19 vaccination was associated with reduced age (OR = 0.53 95% CI 0.43-0.66, P < 0.001), being a resident in other places than Shanghai (OR = 0.40, 95% CI 0.17-0.92, P < 0.05), a shorter time of lockdown (OR = 0.33, 95% CI 0.13-0.83, P < 0.05), a history of other vaccines (OR = 2.58, 95% CI 1.45-4.60, P < 0.01), a fewer number of chronic diseases (OR = 0.49, 95% CI 0.38-0.62, P < 0.001), better knowledge about COVID-19 vaccines (OR = 1.60, 95% CI 1.17-2.19, P < 0.01), and a positive attitude toward COVID-19 vaccines (OR = 9.22, 95% CI 4.69-18.09, P < 0.001).ConclusionAcquiring accurate knowledge and developing a positive attitude toward COVID-19 vaccines are important factors associated with COVID-19 vaccination. Disseminating informed information on COVID-19 vaccines and ensuring efficacious communication regarding their efficacy and safety would enhance awareness about COVID-19 vaccination among older adults and consequently boost their vaccination coverage.